Investments and returns from cooperative and household managed woodlots in Zimbabwe: implications for rural afforestation policy - Jagger, P.; Luckert, M. (Elsevier, 2008)
For several decades, the Zimbabwean government, donors, and NGOs have actively promoted the establishment of cooperative woodlots in Zimbabwe's communal areas. However, despite the provision of considerable extension support and subsidies to these cooperatives, household woodlots are far more common. This paper investigates the motivations of households and groups in Zimbabwe's communal areas to plant trees. Estimates of private economic returns suggest that cooperative woodlots are generally more profitable than household managed woodlots. However, household managed tree planting yields higher economic returns in the absence of subsidized land and other inputs. Statistical analysis indicates that, relative to cooperatively managed woodlots, household managed woodlots tend to be associated with access to non-timber benefits such as windbreaks, and access to market benefits through harvesting. However, relative to cooperatively managed woodlots, household managed woodlots receive less extension advice, and are associated with lower projected private returns because of subsidies provided to cooperative woodlot groups. Although the literature on cooperative management is replete with examples of successful cases, for the case of woodlots in Zimbabwe, it appears as though policy makers may be promoting the wrong management option. Household management of woodlots, rather than cooperative management, may provide greater economic returns, and accordingly better incentives, for the adoption of tree planting.